Pengaruh Etos Kerja, Pelatihan Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Bumi Menara Internusa - Syesilia, Deni; Arif, Mochamad Syaiful (Implementasi Manajemen & Kewirausahaan, 2021)
The main objective of this study is to test and analyze the influence of work ethic, job training and work discipline on employee performance at PT. Earth Tower Internusa. Data collection uses primary data obtained from questionnaires. The sample in this study was an employee of PT. Bumi Menara Internusa Surabaya which numbers 62 people. The analysis used in hypothesis testing is statistical package for the social sciences (SPSS) version 20. The results of this study showed that work ethic had no significant effect on employee performance, job training had a positive and insignificant effect on employee performance, and work discipline had no significant effect on employee performance.